Factors selection fast food among customers in McDonald’s Kota Bharu / Norlaila Ismail - Ismail, Norlaila (Faculty of Business and Management, 2013)
Selection fast food is become a trend nowadays among customers especially students that can contribute to health problem. In this study, the researcher chooses to identify the factor selection fast food among customers in McDonald’s Kota Bharu, Kelantan. Food quality, price and taste are the factors that researcher emphasized in the study. Researcher also needs to find out what are the relationships these factors with selection fast food and which one of these factors that most significant to selection fast food among customer in McDonald’s Kota Bharu. Thus, this study has conducted in McDonald’s Kota Bharu on 300 respondents to be researcher sample. The findings of this indicates that taste is the factor that most significant to selection fast food compare to food quality and price. This study is beneficial to the restaurant in order to increase their profit. It will help them more aware on their main factor of their selection fast food and in turn help them to manage other factors in order to sustain in fast food industry. Future study should focus on the similar study but different factors to any fast food restaurant. By doing this, researcher can clearer picture on the strong factor that contributes customer selecting fast food.